Detection of porcine species DNA on meat processed food samples (shredded meat) using Real-Time PCR - Alfi Sophian; Sri Utaminingsih; Tirta Setya Bhakti; Dewi Rahmawati (Journal of Halal Product and Research)
DNA detection of porcine species in processed meat samples (shredded meat) was carried out as an effort to enrich the literature and reference alternative testing methods in the control of halal products circulating in Indonesia. The purpose of this study was to detect the DNA of porcine species in samples using real-time PCR. The research method used is a qualitative technique. This technique analyzes the CT value of the sample compared to the positive control by looking at the formation of the sigmoid curve if amplification occurs. The controls used consisted of negative control, positive control, other DNA control, and LOD control. The extraction technique used is the column centrifuge technique. The extraction results were then measured using a nano photometer to see the purity and concentration of the extracted DNA. Based on the research, it is known that the extraction results read on a nanophotometer at a wavelength of A260 / A280 show a concentration of 24,350 with a purity value of 21,164. For sample testing, the results of real-time PCR analysis showed the sample was detected at CT 39.77, positive control at CT 31.66, and LOD at 28.32. for negative control and specificity using other DNA was not detected. The conclusion of this research is that the sample used can be detected by the presence of porcine DNA.